2003
DOI: 10.1095/biolreprod.102.003269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Perinatal Maternal Food Restriction on Pituitary-Gonadal Axis and Plasma Leptin Level in Rat Pup at Birth and Weaning and on Timing of Puberty

Abstract: The effects of maternal 50% food restriction (FR) during the last week of gestation and/or lactation on pituitary-gonadal axis (at birth and weaning), on circulating levels of leptin (at weaning), and on the onset of puberty have been determined in rats at birth and at weaning. Maternal FR during pregnancy has no effect at term on the litter size, on the basal level of testosterone in male pups, and on the drastic surge of circulating testosterone that occurs 2 h after birth. At weaning, similar retardation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
93
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 59 publications
7
93
1
2
Order By: Relevance
“…Androgens, corticosteroids and thyroid hormones are among the maternally derived hormones with significant roles during embryonic development in vertebrates. Previous studies showed that ingredient variations in the maternal diet during pregnancy and lactation could affect the pubertal status of female progeny (Cooper et al 1996, Lumey & Stein 1997, Magnusson et al 1999, Adair 2001, Leonhardt et al 2003, Figure 4 Growth curves of two inbred strains of male mice and the direct and reciprocal Fl crosses. N indicates the number of pups included.…”
Section: Discussionmentioning
confidence: 99%
“…Androgens, corticosteroids and thyroid hormones are among the maternally derived hormones with significant roles during embryonic development in vertebrates. Previous studies showed that ingredient variations in the maternal diet during pregnancy and lactation could affect the pubertal status of female progeny (Cooper et al 1996, Lumey & Stein 1997, Magnusson et al 1999, Adair 2001, Leonhardt et al 2003, Figure 4 Growth curves of two inbred strains of male mice and the direct and reciprocal Fl crosses. N indicates the number of pups included.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal food restriction (Leonhardt et al, 2003;Iwasa et al, 2010) or uterine artery ligation (Engelbregt et al, 2000) are associated with late vaginal opening or first estrus. Some authors have reported no effect of maternal food restriction on pubertal development while a single study (Sloboda et al, 2009) found an acceleration of pubertal onset.…”
Section: Abnormal Energy Availability and Timing Of Puberty: Mechanismentioning
confidence: 99%
“…The age of vaginal opening (VO) and the first estrous was delayed, ovarian and testicular growth were drastically retarded and ovulation rate was lower in the undernourished during prenatal period by several kind of animal models in uterine artery ligation, prenatal food or protein restriction and subjected to glucocorticoid overexposure [6][7][8][9][10]. These reports suggest that there is an association between restricted fetal growth and the programming of disease after birth [11][12][13].…”
mentioning
confidence: 99%